2011
DOI: 10.1007/s11095-011-0442-5
|View full text |Cite
|
Sign up to set email alerts
|

The Airways, a Novel Route for Delivering Monoclonal Antibodies to Treat Lung Tumors

Abstract: Delivery of aerosolized-mAbs via the airways deserves further evaluation for treating lung cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…Similar distribution patterns have been observed in previous studies using fluorescently labeled anticancer monoclonal antibodies that compared systemic administration (i.v.) versus local administration via endotracheal aerosolization (20,21). Larger amounts of the MAb in the BAL fluid of mice that received the antibody intranasally may explain the extended protection observed in mice infected up to 5 days after antibody administration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar distribution patterns have been observed in previous studies using fluorescently labeled anticancer monoclonal antibodies that compared systemic administration (i.v.) versus local administration via endotracheal aerosolization (20,21). Larger amounts of the MAb in the BAL fluid of mice that received the antibody intranasally may explain the extended protection observed in mice infected up to 5 days after antibody administration.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages to aerosol administration of medications to the lung include a high local concentration by delivery directly to the airways, a reduced distribution to systemic circulation and, for drugs that would otherwise require subcutaneous or intravenous injection, pain-and needle-free delivery. Several therapeutic agents have been explored for inhalation delivery in malignancies, including chemotherapeutic agents, 20,21 cytokines, 22,23 antisense oligonucleotides 24 and monoclonal antibodies, 25 demonstrating the feasibility of aerosol delivery, potential antitumor effects and reduced side-effects compared to systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that aerosolized cetuximab passed slowly and poorly in blood in mice [103]. It also significantly decreased tumor growth in an ectopic model of lung tumors.…”
Section: Aerosolized Cetuximabmentioning
confidence: 99%